2021
DOI: 10.1177/07399863211044897
|View full text |Cite
|
Sign up to set email alerts
|

Acculturative Stress and the Effects on Health and Health Behaviors in Hispanic Immigrants: A Systematic Review

Abstract: The purpose of this systematic review was to investigate previously published literature that examined the impact of acculturative stress on health in Spanish-speaking populations. The database search yielded a final count of 32 eligible articles for inclusion in this review. Age, acculturative stress measure, and study results were analyzed. Overall, 81.2% of studies investigated the impacts of acculturative stress on mental health with the majority concluding that increased acculturative stress had a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As immigrants immerse themselves into the host culture, there is a gradual exchange between the immigrant’s original values, attitudes, and behaviors and those of the host country [ 30 ]. The process of acculturation could result in poor mental well-being and the adoption of unhealthy behavior, which consequently increases the risk of becoming overweight or obese [ 30 , 31 ]. Although immigrants are found to exhibit better health outcomes than domestic-born populations, a large body of evidence has shown a decline in their health over time [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As immigrants immerse themselves into the host culture, there is a gradual exchange between the immigrant’s original values, attitudes, and behaviors and those of the host country [ 30 ]. The process of acculturation could result in poor mental well-being and the adoption of unhealthy behavior, which consequently increases the risk of becoming overweight or obese [ 30 , 31 ]. Although immigrants are found to exhibit better health outcomes than domestic-born populations, a large body of evidence has shown a decline in their health over time [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acculturation process after immigration is associated with both positive (e.g., improved quality of life) and negative experiences (e.g., discrimination, language barriers, and a sense of not belonging to the US) [ 8 ]. Acculturation stressors are frequently associated with learning a new language, changing the family dynamic, entering into new occupations, dealing with the immigration legal system, and accessing a different healthcare system [ 9 ]. In addition, acculturation stress can be associated with cultural conflict, changes in the family dynamic, and pressure to retain one’s native culture [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research emphasizes that acculturation stress can negatively impact Latinos’ mental and physical health behaviors, such as sleep patterns, cigarette smoking, alcohol consumption, and diet [ 9 , 11 , 12 ]. For example, in a sample of 5,313 Latino adults in the US, it was found that higher levels of acculturation stress were associated with higher insomnia symptom scores [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that rural and low-income areas, as well as racial and ethnic minorities, have higher rates of mental health problems among adolescents and lower rates of detection [20,21]. With the Hispanic population becoming the second-largest racial or ethnic group in the United States [22], it is important to note that Hispanic individuals with mental health disorders are less likely to use mental health services compared to other groups. Furthermore, parental indifference and lack of recognition of their children's mental health status appears to be worse among Hispanic parents [23], resulting in a lower likelihood of Hispanic adolescents receiving appropriate and timely medical treatment [24].…”
Section: Introductionmentioning
confidence: 99%